Impact of Varied Integrated Modules of Yogic Practices on Selected Physiological Variable Among Middle Aged Women - Saroja, S.; Senthil Kumar, M. (Journal of Neonatal Surgery, 2025)
The study goal was to ascertain the Impact of varied integrated yogic practices on chosen physiological variable among middle age women. The study only selected middle aged women (n=60) from the in and around Sivagangai district, Tamilnadu. The age of the subject ranged from the 35 to 55. The subject were separated in to four equal group fifteen each Group - I Asana (n=15), Group- II(n=15) Surya namaskar, Group - III Combined asana and surya namaskar(n=15) and Group- IV control group. The training was conducted thrice in a week for a total of twelve weeks. The training session lasted for 45 minutes. Control group was not involved in any special training. Collected data from experimental and control group were statistically analysed by Analysis of Covariance (ANCOVA) and the dependent "t" test. Data analysis determined that the corrected post-test means' "F" ratio was statistically significant. The conclusion of the study combined asana and Surya namaskar group reduced the diastolic blood pressure more effectively than the Asana and Surya namaskar group